Dalila Cabrita Mateus / Álvaro Mateus, Purga em Angola (Altre Modernità, 2016)
Dalila Cabrita Mateus / Álvaro Mateus, Purga em Angola(Lisboa, Texto Editores, 2009, 206 pp. ISBN 978-972-47-3845-1)di Alexandra Maria de Barros Cruz e Sá